Designing an Android-Based Bisindo Dictionary Application Using the Boyer Moore Method - Agung Kharisma Hidayah; Ujang Juhardi; Rozali Toyib; Nur Ade Wijaya (Penerbit Jurnal Indonesia, 2022)
This research presents the study of application design of Bisindo dictionary with Android-based by using Boyer Moore algorithm. In this reseach, researcher developed it by using Boyer Moore algorithm. This reseach uses the UCD method, which conducts interview toward users of reseach sites, as well as tests on applications or sign language dictionaries, it is BISINDO. From the result of reseach that has been carried out, the Bisindo dictionary (sign language dictionary) can help the learning system for students, teachers, and general people. As the needs feasibility of Indonesia sign language dictionary obtained average scored with excellent information.